Indoor NO Sampling in a Large University Campus in Benin City, Southern Nigeria, Using Palmes Diffusion Tubes - Ukpebor, E. E.; Sadiku, Y. T.; Ahonkhai, S. I. (Biological Sciences - PJSIR, 2005)
Monitoring of NO in different indoor environments (without cooking and with cooking using different fuels) was done. Palmes diffusion tubes were used for the monitoring. The sampling duration was two weeks. The highest NO concentration of 38.61 ppb (73.74 ?g/m3) was monitored in the room where the cooking was done with a gas burner. This was followed by the room with firewood cooking, where the concentration was 36.75 ppb (70.19 ?g/m3) and the least concentration of 24.05 ppb (46.80 ?g/m3) was noted in the room, where kerosene stove was used for cooking. It is of significance to observe that the WHO annual average guideline value of 40 ?g/m3 was exceeded in all the rooms where cooking was done. Levels obtained in this study, therefore, suggest a need for precautionary mitigation. However, the outdoor concentration of NO was almost the same as that obtained indoors in the rooms without cooking. This suggests high penetration indoors of outdoor NO . A background level of 3.40 ppb (6.49 ?g/m3) was established for the environment in Ugbowo, Benin City, Nigeria.